Pengaruh Penambahan Ekstrak Sereh (Cymbopogon nardus) terhadap Aktivitas Antioksidan, Karakteristik Fisikokimia, dan Tingkat Kesukaan Minuman Instan Kunir Putih (Curcuma mangga Val.) sebagai Minuman Fungsional Berbasis Rimpang Lokal - Puswanto Puswanto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
White turmeric (Curcuma mangga Val.) is one of Indonesia’s local rhizome plants containing curcuminoids and polyphenolic compounds, which have potential as natural sources of antioxidants. This study aimed to evaluate the effect of different levels of lemongrass extract addition on antioxidant activity, physicochemical characteristics, and consumer preference of white turmeric instant beverages, as well as to determine the optimal formulation. The beverage was prepared using 500 ml of white turmeric extract with the addition of lemongrass extract at concentrations of 100, 200, 300, and 400 ml through a crystallization method. A Completely Randomized Design (CRD) with two replications was applied, and hedonic testing was conducted using 20 semi-trained panelists. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that lemongrass extract addition significantly increased antioxidant activity and color intensity and affected aroma preference, but did not significantly influence moisture content. The formulation with 100 ml lemongrass extract obtained the highest sensory acceptance, while the 400 ml formulation showed the highest antioxidant activity. The optimal formulation was recommended at 100–200 ml lemongrass extract addition to produce a functional beverage with a balance between health benefits and consumer acceptability.